Analisis Gaya Kepemimpinan dalam Peningkatan Kinerja Organisasi IPNU IPPNU Desa Kedungboto - Zidny Camelia; Wahyu Eko Pujianto (Jurnal Publikasi Ilmu Manajemen, 2024)
Leadership style analysis involves an in-depth understanding of how a leader leads and influences team or organization members. The purpose of this study is to evaluate the leadership style in improving the performance of the IPNU IPPNU organization in Kedung Boto Village. A qualitative approach was used as the research method, and a qualitative descriptive research type involves information in the form of words both written and oral from the observed subjects. The data collection process was conducted through interviews, observation, and documentation. The results showed that the IPNU-IPPNU organization in Kedung Boto Village applies a democratic leadership style. The strategy applied to increase organizational participation involves a systematic approach such as the formulation of work programs, implementation of work programs, and evaluation related to the program. Supporting factors include open and clear communication, inspirational leadership, member empowerment, shared goal setting, and an organizational culture that encourages participation. In contrast, inhibiting factors involve organizational characteristics, the environment, the level of activeness and discipline of organizational members, and suboptimal policies or practices in the field.